The prevalence of drug abuse among the students of Zahedan - Sayed Aliakbar Refahi; Saeid Mohtasham; Mohammad Reza Raeisoon (Gonabad University of Medical Sciences, 2018)
Addictive substance abuse is one of the most important problems of human societies and one of the major challenges to the social, health and political world. Although the problem is not confined to specific age groups, young people, including university students, are among the main groups at risk. Therefore, this study examined the prevalence of addictive substance abuse among students of Islamic Azad university, Zahedan. This descriptive, cross-sectional study was conducted on 1014 students studying at the Islamic Azad University of Zahedan, using the cluster sampling method, in due observance of gender, college, and program level distribution. The data were collected using the high-risk behaviors questionnaire and a demographics form. The greatest frequencies comprised, respectively, of waterpipe smoking (40.04%), cigarette (22%), alcohol (12.06%), and opium (7.5%). Smoking prevalence in male and female students were respectively 56.7% and 26.1%. Cigarette smoking rates among female and male students were of 6.8% and 39.1% prevalences. Alcohol consumption among female and male students had 2.4% and 13.5%. Study results indicate a high prevalence of drug abuse among students was addiction. This demands greater attention to preventive and educational measures and interventions for this vulnerable group of society.